2020
DOI: 10.1371/journal.pbio.3000595
|View full text |Cite
|
Sign up to set email alerts
|

A role for triglyceride lipase brummer in the regulation of sex differences in Drosophila fat storage and breakdown

Abstract: Triglycerides are the major form of stored fat in all animals. One important determinant of whole-body fat storage is whether an animal is male or female. Here, we use Drosophila, an established model for studies on triglyceride metabolism, to gain insight into the genes and physiological mechanisms that contribute to sex differences in fat storage. Our analysis of triglyceride storage and breakdown in both sexes identified a role for triglyceride lipase brummer (bmm) in the regulation of sex differences in tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
105
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(121 citation statements)
references
References 158 publications
(268 reference statements)
16
105
0
Order By: Relevance
“…We focused on looking at TAG since proper mobilization of lipid stores has been shown to be essential for starvation tolerance in Drosophila. Both NORMOXIC males and females showed a decrease in total TAG levels following starvation, with this effect being more pronounced in males, a previously reported result that is consistent with mobilization of lipid stores in nutrient deprived conditions (Gronke et al, 2007; Wat et al, 2020). In contrast, HYPOXIC animals showed a sexually dimorphic response to starvation.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…We focused on looking at TAG since proper mobilization of lipid stores has been shown to be essential for starvation tolerance in Drosophila. Both NORMOXIC males and females showed a decrease in total TAG levels following starvation, with this effect being more pronounced in males, a previously reported result that is consistent with mobilization of lipid stores in nutrient deprived conditions (Gronke et al, 2007; Wat et al, 2020). In contrast, HYPOXIC animals showed a sexually dimorphic response to starvation.…”
Section: Resultssupporting
confidence: 83%
“…However, we also found that both male and female HYPOXIC animals showed a defect in lipid mobilization upon starvation, and that these effects were sexually dimorphic. In the case of males, the NORMOXIC control group showed a reduction in total TAG levels following starvation - a phenotype that has been reported before and is consistent with mobilization of lipid stores to support survival during nutrient starvation (Gronke et al, 2007; Palanker et al, 2009; Wat et al, 2020). However, we found that this decreases in TAG levels was significantly exacerbated in the HYPOXIC group, who showed an almost complete depletion of their lipid stores.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Recent discoveries indeed suggest important, but largely uncharacterized roles for LDs in this cell type (Pennetta & Welte, 2018;Wat et al, 2020).…”
Section: Broader Insights Into Protein Sequestrationmentioning
confidence: 99%